Assessment of School Essentials in Nepal - Dhobi, Saleem (Patan Prospective Journal, 2023)
This paper examines the importance of educated and trained teachers, updated curricula, latest technologies, efficient management committee, school buildings with spacious playgrounds in executing the educational plans formulated to impart quality education to the youths of the current generation so that they can contribute to the future development of Nepal reaching different positions and places. How can schools perform better and what are the necessities that help to cater quality education? The objective of the article is to revitalize the initiatives be taken and would be taken for the holistic development of the education and educational institutions that are committed to fueling the country with the quality human resources that can affect the multidimensional development in varied approaches. The findings of the paper have been that the digital competencies tremendously significant that can boost up the pedagogical approach. The quality of teachers determines the standard of the schools whether they are public or private. The exploration reveals that the role of frequent training and conferences is indispensable in capacitating the teachers who are one of the most crucial aspects of the educational institutions. The research demonstrates that without the development and motivation of the teachers, even advanced curricula and sophisticated buildings cannot be adequate enough to execute the education plan to ensure quality education. Therefore, the focus of the school management must be on the development of teachers’ competence and career for the sustainable development of the academic institutions.